2020
DOI: 10.1172/jci129642
|View full text |Cite
|
Sign up to set email alerts
|

Follicular T helper cells shape the HCV-specific CD4+ T cell repertoire after virus elimination

Abstract: BACKGROUND. Chronic hepatitis C virus (HCV) infection is characterized by a severe impairment of HCV-specific CD4 + T cell help that is driven by chronic antigen stimulation. We aimed to study the fate of HCV-specific CD4 + T cells after virus elimination. METHODS. HCV-specific CD4 + T cell responses were longitudinally analyzed using MHC class II tetramer technology, multicolor flow cytometry, and RNA sequencing in a cohort of patients chronically infected with HCV undergoing therapy with directacting antivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 56 publications
3
47
0
1
Order By: Relevance
“…Recent studies have investigated class II tetramer binding CD4 + T cells in chronic HCV infection and their fate after virus clearance. In an elegant study with samples from 44 patients tested at baseline, during and after DAA-mediated cure, Smits et al [ 47 ] showed a significant increase in HCV tetramer binding CD4 + T cells within 2 weeks of therapy initiation. This likely reflects the egress of virus-specific cells from the liver in an IP-10 gradient-dependent mechanism.…”
Section: Adaptive Immune Lymphocytes During and After Clearance Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have investigated class II tetramer binding CD4 + T cells in chronic HCV infection and their fate after virus clearance. In an elegant study with samples from 44 patients tested at baseline, during and after DAA-mediated cure, Smits et al [ 47 ] showed a significant increase in HCV tetramer binding CD4 + T cells within 2 weeks of therapy initiation. This likely reflects the egress of virus-specific cells from the liver in an IP-10 gradient-dependent mechanism.…”
Section: Adaptive Immune Lymphocytes During and After Clearance Ofmentioning
confidence: 99%
“…The impact of virus clearance on these exhaustion and activation markers on CD4+ T cells is well documented. The frequency of virus-specific CD4 + T cells expressing PD-1, BTLA, and T cell Ig and ITIM domain (TGIT) stays high during and after treatment, although intensity of PD-1 expression is reduced significantly [ 47 ]. Higher levels of TIGIT expression on HCV-specific CD4 + T cells observed during CHC remains persistently elevated at least until 24 weeks from the end of DAA treatment [ 53 ].…”
Section: Adaptive Immune Lymphocytes During and After Clearance Ofmentioning
confidence: 99%
See 3 more Smart Citations